Anaerobic fitness assessment in taekwondo athletes: A new perspective - Rocha,Fernando (2016)
We intended to determine the concurrent validity of a taekwondo specific anaerobic test (TSAT) to assess anaerobic fitness in taekwondo athletes. Seventeen elite male subjects (17.59 ± 4.34 years of age; 1.72 m ± .07 m in height; 61.3 kg ± 8.7 kg in weight and 15.6% ± 8.5% in body fat) performed a TSAT, which consisted of kicking a punching bag for 30 seconds. The standard test was the Wingate Anaerobic Test. Two trials were made for both tests and the agreement between both was tested. The variables analysed and compared were: peak power; relative peak power; mean anaerobic power; relative mean anaerobic power; fatigue index and anaerobic capacity. The number of kicks performed in the TSAT protocol and the maximum height of the counter movement jump (CMJ) were also registered. Trial I and II had significant ICC results in all variables (P = .000) ranged between 0.56 and 0.97. Both protocols were significantly correlated (r = 0.55 to 0.88; P = .000 to .05). CMJ strongly correlated with the number of techniques (r=0.59; P = .013) and the mean power (r = 0.56; P = .019) of the TSAT. The variables between the two methods correlate and are consistent, except for the anaerobic capacity that although correlated, is not consistent with constant bias, P = 0.001; CI]-705.1;-370.2[. TSAT has a level of agreement with the Wingate, and assigns specificity in the evaluation of these variables.